ATTRACTION DEVELOPMENT STUDIES IN COMPLEX MANDE RUBIAH HOUSE IN LUNANG VILLAGE LUNANG DISTRICT OF PESISIR SELATAN REGION - ANITA, ROSA; Drs. Edi Suarto, M.Pd, Drs. Edi Suarto, M.Pd; Yuherman, SP., M.Pd, Yuherman, SP., M.Pd (Pendidikan Geografi, 2014)
ABSTRACT   This study aimed to obtain information, and analyze public perception about Attraction development of MandehRubiah house in Lunangvillage Lunang district of Pesisir Selatan Region views of: 1) the condition of attraction, 2) development constraints attractions and 3) efforts in the development of attraction. This research is a qualitative study, conducted at the MandehRubiah house in Lunang village Lunang district of Pesisir Selatan Region. Informants in this study were drawn snowball sampling, making the subject of research conducted directly and ask the subject on a rolling basis. Informants of this study is the Head of the Department of Tourism Arts and Culture Pesisir Selatan Region, camatLunang, WaliNagariLunang, managers, community leaders and visitor MandeRubiah House Complex. The number of informants in the study were limited in what amounts to researchers find new data or new answers.Results showed : 1) MandeRubiah house development as a tourist destination in MandehRubiah house in Lunang village Lunang district of Pesisir Selatan Region, current conditions deteriorated, damaged road conditions, condition of facilities and infrastructure to support tourism and yet incomplete optimal governments focus on developing attraction, 2 ) MandeRubiahhouse  difficulties in the development of facilities and lack of infrastructure and lack of publicity and promotion 3) Development carried out at the MandeRubiah house is to equip the facilities and infrastructure still lacking and damaged as well as water closed and raise public awareness of the existence of attraction.